Taxonomic revision of Zingiber (Zingiberaceae) of Taiwan - Lin, Yuan-Chien; Chao, Chien-Ti; Chang, Chih-Yi; Tseng, Yen-Hsueh (European Journal of Taxonomy, 2022)
The genus Zingiber contains about 180 species distributed mainly in tropical regions. Several species of Zingiber are cultivated globally for their medicinal and culinary value, such as true gingers (Z. officinale), bitter gingers (Z. zerumbet), and Z. purpureum. In Taiwan, two endemic species and one incompletely known taxon were recorded in the last edition of Flora of Taiwan, and several taxonomic issues still remain unresolved. Therefore, we revised the Taiwanese Zingiber based on morphological, palynological, anatomical, and molecular evidence, as well as their distribution. The results showed that floral characters such as labellum, fertile bracts, and corolla tubes are of great taxonomic value in distinguishing taxa of Zingiber of Taiwan. Accordingly, five species are treated in the present study, namely Z. chengii Y.H.Tseng, C.M.Wang & Y.C.Lin, Z. mioga Thunb., Z. oligophyllum K.Schum., Z. pleiostachyum K.Schum., and Z. shuanglongense C.L.Yeh & S.W.Chung. Zingiber mioga might be a newly naturalized species to Taiwan. Zingiber kawagoii Hayata and Z. koshunense C.T.Moo are treated as synonyms of Z. pleiostachyum.